VOLUME BLOOD FLOW IN LARGE ARTERIES AMONG ELDERLY PATIENTS WITH ARTERIAL HYPERTENSION AND VARIOUS LEVELS OF BLOOD PRESSURE - G. G. Efremushkin; T. V. Filippova; E. A. Denisova (Российский кардиологический журнал)
To investigate volume, velocity, and energy hemodynamic parameters of large arteries among elderly patients with arterial hypertension (AH), 50 AH men, aged 62-88 years (mean age 76,3±0,9 years; mean AH duration 16,0±1,2 years) were examined. Duplex ultrasound of common carotid artery (CCA), brachial artery (BA), and femoral artery was performed. For each large artery, the following hemodynamic parameters were calculated: blood flow volume per 1 second (Q, cm3/s) in each phase, total (all phases) blood flow volume per 1 minute, and kinetic energy (hV) of pulse wave (PW). In elderly AH patients, compared to healthy controls, blood flow volume per 1 minute was increased, with blood flow redistributed towards CCA and BA. The magnitude of these changes was the largest in patients with elevated maximal and minimal blood pressure (BPmax, BPmin). In AH subjects with normal BP and isolated systolic AH (ISAH), blood flow volume in large arteries was higher than in healthy individuals, but lower than in AH patients with elevated BPmax and BPmin. BP level was determined by the energy parameter of PW (hV). Compared to healthy individuals, the highest hV value was observed in ISAH patients. PW with high hV resulted in earlier first tones and lower last tones under the cuff, which led to higher BPmax and normal or lower BPmin values. Increased tone of BA wall resulted in last tones being registered at higher cuff pressure levels and, therefore, increased systolic BPmax and BPmin in AH patients.